ANALISIS PERTUMBUHAN ENDOGEN DALAM OTONOMI DAERAH - Ismawan, Bambang (Journal of Indonesian Economy and Business, 2003)
Decentralization era is a momentum for mobilizing local resources to develop localcapital. Microfinance is the key to capital formation at the local level, solve the bigproblem of poverty and empower peopleâs socio economy. The strength of microfinance is based on people driven and itâs sustainability. Microfinance will contribute broad based development and development through equity.Keywords: Accessibility, peopleâs economy, self reliance, microfinance, microenterprise, sustainability